In Vitro Investigation of Heat Transfer Phenomenon in Human Immature Teeth - Maryam Talebi; Sahar Moghimi; Mina Shafagh; Hadi Kalani; Fatemeh Mazhari (Tabriz University of Medical Sciences, 2014)
Background and aims. Heat generated within tooth during clinical dentistry can cause thermally induced damage to hard and soft components of the tooth (enamel, dentin and pulp). Geometrical characteristics of immature teeth are different from those of mature teeth. The purpose of this experimental and theoretical study was to investigate thermal changes in immature permanent teeth during the use of LED light-curing units (LCU). Materials and methods. This study was performed on the second mandibular premolars. This experimental investiga-tion was carried out for recording temperature variations of different sites of tooth and two dimensional finite element mod-els were used for heat transfer phenomenon in immature teeth. Sensitivity analysis and local tests were included in the mod-el validation phase. Results. Overall, thermal stimulation for 30 seconds with a low-intensity LED LCU increased the temperature from 28°C to 38°C in IIT (intact immature tooth) and PIT (cavity-prepared immature tooth). When a high-intensity LED LCU was used, tooth temperature increased from 28°C to 48°C. The results of the experimental tests and mathematical modeling il-lustrated that using LED LCU on immature teeth did not have any detrimental effect on the pulp temperature. Conclusion. Using LED LCU in immature teeth had no effect on pulp temperature in this study. Sensitivity analysis showed that variations of heat conductivity might affect heat transfer in immature teeth; therefore, further studies are re-quired to determine thermal conductivity of immature teeth.